Perbedaan Efektivitas Aromaterapi Lavender Dan Aromaterapi Peppermint Terhadap Nyeri Pada Pasien Post Sectio Caesarea Di Rsud Ajibarang - Safaah, Siti; Purnawan, Iwan; Sari, Yunita (Journal of Bionursing, 2019)
Background: Options delivery birth process through the SC in Indonesia is increasing, so the risk of complications post SC also growing. One complication that arises is wound pain post SC. Treatment of pain in post SC are 2 kinds, which are pharmacological and non-pharmacological. One handling non-pharmacological use aromatherapy. Aromatherapy that popularly used are lavender and peppermint. Both of these aromatherapy can reduce pain and have few side effects.Objective: This study aims to determine differences in the effectiveness aromatherapy lavender and peppermint. Methodology: This experimental study applied experiment with pre- and post-test control group design. Samples taken were 32 with consecutive sampling. This study was divided into 2 groups : intervention group (lavender) and control group (peppermint). The data were analyzed using Wilcoxon test and Mann Whitney. Results: Characteristics of respondents in the age range 26-35 years by 68.8% in the peppermint group and 75% in the group of lavender. Test Wilcoxon showed that there is significant pain reduction both in the group of lavender or peppermint group, this is indicated by the value of p= 0.000. But the Mann-Whitney test showed a decrease in pain on lavender larger group than the group of peppermint, which is the value of p= 0.005.Conclusion: Aromatherapy lavender is more effective than peppermint aromatherapy in reducing pain post SC.